Who’s kidding whom in Macau’s English performance? - Morrison, Keith (Macau Business, 2021)

What's behind Macau's business disaster? - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Business 101. When companies plan their business models, typically they must consider, amongst other matters: their products and/or services; demand; market(s) and their environments (economic, political, cultural, social); existing, potential, and likely competition; start-up and ongoing costs and expenses; emergency funding; marketing and promotion; income streams, revenue, and delayed profit; sales; distribution; cash flow; profit margins, gross and net; liabilities; risk analysis, evaluation, and handling; constraints and the ‘what if’ factor; flexibility, adaptability, and adjustment.

Undergraduate students in part‐time employment in China - Tam Oi I, Betty; Morrison, Keith (Educational Studies, 2005)

Twilight of the idols - Morrison, Keith (Macau Business, 2021)

Travel Sickness - Morrison, Keith (Macau Business, 2021)

Toward an educational agenda for Macau at the start of the new millennium - Morrison, Keith (China Perspectives, 2003)

Tipping points and economic recovery in Macau - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | New year; old problem. As the pandemic rolls on, so many calls for economic diversification in Macau as a survival strategy have been heard, loud and long, that, as the law of diminishing returns tells us, their effects recede.

Three cheers for critical thinking | Macau Business - Morrison, Keith (Macau Business, 2021)

The wonderland of Macau's talent development - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | The world is full of interesting paradoxes that befuddle the mind. Or, as the delightful chapter in Alice in Wonderland put it: ‘‘curiouser and curiouser!’’.

The truth, the whole truth, and nothing but the truth - Morrison, Keith; van der Werf, Greetje (Educational Research and Evaluation, 2020)

The scourge of construction - Morrison, Keith (Macau Business, 2022)

The scalpel model of educational research - Morrison, Keith; van der Werf, Greetje (Educational Research and Evaluation, 2020)

The poverty of curriculum theory: a critique of Wraga and Hlebowitsh - Morrison, Keith R. B. (Journal of Curriculum Studies, 2004)

The international recruitment obstacle race in Macau - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Macau’s development of international and tertiary sector industries is the watchword for its long-overdue diversification. Is Macau ready for this?

The Genesis of a New Year | Macau Business - Morrison, Keith (Macau Business, 2021)

The curriculum handbook - Brown, Terry; Morrison, Keith (Longman, 1990)

The Colonization of Lifeworlds of Education by Work: Restoration and Recoupling of Lifeworld and System in the Inner Self - Morrison, Keith (Horizons of Education, 2015)
The argument is raised that, in an age of the networked, connected society in an information-rich environment with communication possibilities as never before experienced or made possible, the displacement of educational virtues of morality, ethics and the development of all-round human beings, by those of money, labour, power and work are speeding apace, and the disconnect between system and lifeworld is increasing. Drawing initially on the work of Habermas, in which the colonization of the lifeworld occurs by system imperatives of rationalization, labour, money and power, the paper argues that such moves are manifested starkly in discourses of the relation between education and work, and five areas are introduced in which the links operate. The marketization and commodification of education, together with its incorporation into the service of capital and labour, are attested through a short worked example of one small territory within the larger context of China. Then, taking a lead from Sertillanges and Habermas’s later work, the paper argues for: (a) a reaffirmation of the importance of moral, ethical and spiritual dimensions of education; (b) the breaking of a narrowly instrumental, capital-acquisitive view of education as serving the jobs market and social control and towards a liberating view of education as communicative action and the development of being rather than simply behaving; (c) the importance of transcendence and immanence; and, thereby, (d) moves towards the re-integration of system and lifeworld in participating subjects.

The business of social justice in Macau - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | As Macau rebuilds its post-pandemic economy, one could be forgiven for believing that the good life for all has arrived, as evidenced in the manifest opulence on display in its up-market shopping malls. However, this is not the case; social justice needs attention in Macau.

The academic and intellectual life of Macau - Morrison, Keith (Review of Culture (Revista de Cultura), 2014)

Testing to Destruction: A problem in a small state - Morrison, Keith; Joan, Tang Fun Hei (Assessment in Education: Principles, Policy & Practice, 2002)

Taming randomized controlled trials in education: exploring key claims, issues and debates - Morrison, Keith (Routledge, Taylor & Francis Group, 2021)
"There is a recent surge in the use of randomized controlled trials (RCTs) within education globally, with disproportionate claims being made about what they show, 'what works', and what constitutes the best 'evidence'. Drawing on up-to-date scholarship from across the world, Taming Randomized Controlled Trials in Education critically addresses the increased use of RCTs in education, exploring their benefits, limits and cautions, and ultimately questioning the prominence given to them. While acknowledging that randomized controlled trials do have some place in education, the book nevertheless argues that this place should be limited. Drawing together all arguments for and against RCTs in a comprehensive and easily accessible single volume, the book also adds new perspectives and insights to the conversation; crucially, the book considers the limits of their usefulness and applicability in education, raising a range of largely unexplored concerns about their use. Chapters include discussions on: The impact of complexity theory and chaos theory Design issues and sampling in randomized controlled trials Learning from clinical trials Data analysis in randomized controlled trials Reporting, evaluating and generalizing from randomized controlled trials. Considering key issues in understanding and interrogating research evidence, this book is ideal reading for all students on Research Methods modules, as well as those interested in undertaking and reviewing research in the field of education"--
Keywords: Clinical trials; Education; Educational indicators; Research Data processing; Research Methodolgy

Sustainable development or survival of Macau? - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | In June of this year, a publication entitled ‘Macau’s sustainability and diversification’ noted that Macau’s ‘economic volatility caused by an unbalanced industrial structure restricts the diversified development of society. Economic diversification is the only way for Macau to achieve sustainable development’. Nothing new there, and, anyway, such a singular view is unconvincing. What about other aspects of society? Diversity is not singular, and it requires inclusion.

Sunshine and shadows - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | The recent euphoria over Macau’s economic resurrection should not mask the long-standing challenges facing its society and values. Sunshine creates shadows in which can lurk a range of pathologies.

Suicide prevention in schools: are Macau's teachers prepared? - Días, Javier Suárez; Morrison, Keith (Macau Inter-University Institute, 2005)
Keywords: China Macau (Special Administrative Region); Prevention; Students; Suicidal behavior; Suicide; Teenagers

Student engagement, higher education, and social justice: beyond neoliberalism and the market - Bramley, Corinna; Morrison, Keith (Routledge, 2023)
"Student engagement is a catch-all term, irresistible to educators and policy makers, and serving many agendas and purposes. This ground-breaking book provides a powerful theory of student engagement, rooted in critical theory and social justice. It sets out a compelling argument for student engagement to promote social justice and to repel neoliberalism in, and through, higher education, addressing three key questions: -Student engagement in what? -Student engagement for what? -Student engagement for whom? The answers draw on Habermas, Honneth, Gramsci, Foucault, and Giroux in examining ideology, power, recognition, resistance, and student engagement, with examples drawn from across the world. It sets out key features, limitations and failures of neoliberalism in higher education, and indicates how student engagement can resist it. Student engagement calls for higher education institutions to be sites for challenge, debate on values and power, action for social justice, and for students to engage in the struggle to resist neoliberalism, taking action to promote social justice, democracy, and the public good. This book is essential reading for educators, researchers, managers and students in higher education, social scientists and social theorists. It is a call to reawaken higher education for social justice, human rights, democracy and freedoms"--
Keywords: Active learning; Education, Higher; Neoliberalism; Social aspects; Social justice and education

Structuration theory, habitus and complexity theory: elective affinities or old wine in new bottles? - Morrison, Keith (British Journal of Sociology of Education, 2005)

Simplicity and Complexity in Contemporary School Leadership: A Response to Grace - Morrison, Keith (British Journal of Educational Studies, 2001)

Sensitive educational research in small states and territories: the case of Macau - Morrison, Keith (Compare: A Journal of Comparative and International Education, 2006)

Searching for causality in the wrong places - Morrison, Keith (International Journal of Social Research Methodology, 2012)

School leadership and complexity theory - Morrison, Keith (Routledge/Falmer, 2002)
Keywords: Complex organizations; Educational leadership; School management and organization

School inspection in small states and territories: an overview and case study of Macau - Morrison, Keith (Compare: A Journal of Comparative and International Education, 2009)

Santa Claus is not coming to everyone in Macau - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Macau Business | December 2023 Keith Morrison – Author and educationist

Review of Gorard, S. (2020) Getting evidence into education: evaluating the routes to policy and practice - Morrison, Keith (Educational Research and Evaluation, 2020)

Review of Biesta. G. (2020) Educational research: an unorthodox introduction, Educational Research and Evaluation - Morrison, Keith (Educational Research and Evaluation, 2020)

Research Methods in Education - Cohen, Louis; Manion, Lawrence; Morrison, Keith (Routledge, 2007)

Research Methods in Education - Cohen, Louis; Manion, Lawrence; Morrison, Keith (Routledge, 2013)

Research methods in education - Morrison, Keith; Cohen, Louis; Manion, Lawrence (Routledge, 2018)

Replication research in education: a guide to designing, conducting and analysing studies - Morrison, Keith (Routledge, 2022)
"Providing an overview of key issues in theory and practice, Replication Research in Education is designed to identify and discuss the benefits and challenges facing replication studies in education. Both clear and practical, this ground-breaking volume covers how to introduce, develop, conduct, report and discuss these studies, and the issues they raise for policy and practice. Bridging theory and practice, this book considers what replication research should look like, how it should be conducted and how to judge when it has been successful. It enables researchers to plan and conduct studies successfully, from their earliest stages through to completion. This key text: brings together in a single volume, existing issues, claims and counter-claims, discourses and practices of replication introduces, covers, and extends this field of research, indicating its possibilities and limits expands and adds to existing discussions and practices will enable researchers to design, conduct, evaluate and critique studies. The comprehensive and exhaustive coverage of issues and practices within Replication Research in Education make it a "must read" for all novice and experienced educational researchers who are considering, conducting, and reviewing replication studies in education"--

Realizing the promises of replication studies in education - Morrison, Keith (Educational Research and Evaluation, 2019)

Randomised Controlled Trials for Evidence-based Education: Some Problems in Judging 'What Works' - Morrison, Keith (Evaluation & Research in Education, 2001)

Prize-giving time for Macau - Morrison, Keith (Macau Business, 2020)

Planning and accomplishing school-centred evaluation. - Morrison, Keith (Peter Francis, 1993)

Pedagogy in higher education - Morrison, Keith (Chinese Cross Currents, 2005)

Paradox Lost: Toward a Robust Test of the Chinese Learner - Morrison, Keith (Education Journal, 2006)
This article suggests that attempts to date to unravel the paradox of the Chinese learner are incomplete and inadequately modeled, and that the complexities of the paradox have not yet been fittingly operationalized or alternative explanations of research data investigated. It contends that attempts either to state or to unravel the paradox are chimerical, as they risk oversimplifying a complex phenomenon, the extent and nature of which are insufficiently understood to date. The article argues that investigating the phenomenon of Chinese learners' strong performance in international measures of achievement requires researchers to operate more rigorously in their search for alternative and multiple explanations of results in terms of causality, sampling, and representing heterogeneity. Several explanations of data on the paradox are presented, and alternative explanations which might be more usefully explored are provided. The article also questions the extent to which research on the Chinese learner, with a search for a unitary set of characteristics, is not, itself, prey to totalizing, collectivist ideologies cast in unrealistic meta-narratives. Recommendations are made for further research.

Online and paper evaluations of courses: a literature review and case study - Morrison, Keith (Educational Research and Evaluation, 2013)

Mind your own business - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Across the world, a civil service job pays well and is secure. Not bad if you can get it, with competitive entry to it by hordes of applicants.

Methods, understandings, and expressions of causality in educational research - Morrison, Keith; van der Werf, Greetje (Educational Research and Evaluation, 2020)

Men and women in employment in Macau: A longitudinal survey of inequality. - Morrison, Keith (Journal of Macau University of Science and Technology, 2009)

Measuring and Targeting Internal Conditions for School Effectiveness in the Free State of South Africa - Kgaile, Abraham; Morrison, Keith (Educational Management Administration & Leadership, 2006)
A questionnaire-based methodology for constructing an overall index of school effectiveness is reported, focusing on within-school conditions of schools, which is currently being used in the Free State of South Africa. The article reports the construction and use of a straightforward instrument for measuring the effectiveness of key aspects of the conditions for school effectiveness in the Free State, using a variety of dimensions. It indicates how this instrument can identify where to intervene in improving schools in order to gain the maximum return on investment of time, effort, development activity and support. The instrument provides aggregated and disaggregated data for individual schools, groups of schools and whole districts, both at a single point in time and over time, thereby enabling the most economical and beneficial development to be planned for targeted individual schools and groups of schools. It enables users to identify the key drivers of the internal school conditions for effectiveness, development and change in schools.

Managing complex change in school: engaging pedagogy, technology, learning and leadership - Garcia, Alejandro Salcedo; Morrison, Keith (Routledge, 2014)
Keywords: EDUCATION / Educational Policy & Reform / General; EDUCATION / Evaluation; EDUCATION / Leadership; Educational change; Educational leadership; Educational technology

Management Theories for Educational Change - Morrison, Keith (SAGE Publications Ltd, 1998)

Macau’s gaming culture hits higher education - Morrison, Keith (Macau Business, 2021)

Lone parents' experiences as higher education students: learning to juggle - Morrison, Keith (Educational Research and Evaluation, 2013)

Linguistic and economic capital in Macau - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Macau wisely looks to mainland China, South-East Asia, and Portuguese-speaking countries, as part of its economic diversification. However, to be a player on the international stage and world-wide market, it must look wider, and, hence, the standard of English in Macau must improve dramatically and urgently.

Life Is not a Walk across a Field - Morrison, Keith (European Scientific Institute, 2024)

Leadership for self-organisation: complexity theory and communicative action - Morrison, Keith (International Journal of Complexity in Leadership and Management, 2011)

Interviewing children in uncomfortable settings: 10 lessons for effective practice - Morrison, Keith (Educational Studies, 2013)

Improving Teaching and Learning in Higher Education: Metaphors and Models for Partnership Consultancy - Morrison, Keith (Evaluation & Research in Education, 2003)

Implementing cross-curricular themes - Morrison, Keith (2018)

Ideology, Linguistic Capital and the Medium of Instruction in Hong Kong - Morrison, Keith; Lui, Icy (Journal of Multilingual and Multicultural Development, 2000)

Human capital investment outflanked by Macau's needs - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | As Macau strives to revive its post-pandemic economy and to reinject life into its ailing society, calls for investment in human capital resurface, alongside endless mantras of economic diversification which, for years, seem to have fallen on deaf ears, and together with plans for further infrastructure development and construction which have already turned Macau into a concrete jungle.

How suitable are you for Macau’s workforce? - Morrison, Keith (Macau Business, 2021)

Higher Education in Macau: waxing or waning? - Morrison, Keith (Macau Business, 2021)

Group work and cultural characteristics in a Chinese school - Morrison, Keith; Garcia, Alejandro Salcedo; Wong, Sin Teng (Educational Research and Evaluation, 2020)

Getting the agenda right for higher education in Macau - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Here we are, at the start of a new academic year in Macau’s higher education (HE). What will students learn? What kind of people are the institutions turning out? For example, look at the thousands of students studying business and technology in Macau, the big recruiters in HE.

Getting out of a problem - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Macau should be proud of its protective handling of the Covid-19 pandemic, as it has managed to contain its spread, and many of its citizens have been able to lead a more normal life than in other parts of the world. We should be grateful for this.

Games of chance - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Here we are, back in full-throttle summer tourism in tiny Macau, with visitors galore, lines of tourist coaches everywhere, and the casinos back on course to welcome gamblers. However, gambling reaches much wider than Macau’s casinos.

From ‘Mixed Methods’ to ‘Integration’ in Social Science Research - Morrison, Keith (Symposium European Scientific Institute, 2023)

Escape from Macau - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Macau used to be very appealing to expatriates from across the world. Its low tax rate (and zero tax for low-paid expatriates), blends of cultures, business opportunities, life style, history, unique features and a host of other attractions fuelled an ongoing supply of foreign nationals to this small, unusual city. It is an interestingly idiosyncratic place in which to live. For many expatriates, Macau has been home, in many cases reaching back more than one generation. This is perhaps unsurprising, as people here are typically exquisitely polite, a delight to be with, and very accepting. Its acceptance of differences in values is an example to countries across the world. Macau is a safe place to live.

Educational Philosophy and the Challenge of Complexity Theory - Morrison, Keith (Educational Philosophy and Theory, 2008)

Dreaming of diversification - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Once upon a time there was a cockerel who succumbed to flattery when a wily fox told him that he had the most magnificent singing voice, especially when he sang with his eyes closed tightly.

Does repeating a year improve performance? The case of teaching English - Morrison, Keith; Ieong On No, Anna (Educational Studies, 2007)

Curriculum planning and the primary school - Morrison, Keith; Ridley, Ken (Chapman, 1988)

Copycat Macau? - Morrison, Keith (Macau Business, 2021)

Conditional internationalism in Macau - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Just when diversification is the name of the game in Macau, and with the manifold benefits of diversity that internationals can bring, how sensible is it to treat its international non-resident workers so poorly, and with lamentable transparency and accountability?

Conceptual replications, research, and the “what works” agenda in education - Morrison, Keith (Educational Research and Evaluation, 2022)

Complexity Theory, School Leadership and Management: Questions for Theory and Practice - Morrison, Keith (Educational Management Administration & Leadership, 2010)
Complexity theory (CT) has had a meteoric rise in management literature and the social sciences. Its fledgling importation into school leadership and management raises several questions and concerns. This article takes one view of CT and argues that, though its key elements have much to offer school leadership and management, caution has to be exercised in accepting CT too readily, as it: (1) is unclear on its own novelty, nature and status; (2) can be regarded as disguised ideology in conflating description and prescription; (3) confuses explanation with prediction; (4) is relativist, undermining its own status; (5) contains problems in its advocacy of self-organization; (6) neglects the ethical and emotional dimensions of leadership and management; and (7) risks exonerating school leaders and managers from reasonable expectations of accountability and responsibility. The article concludes that there are questions to CT at the levels of theory, ontology, deontology and ethics, but that it offers useful challenges for school leadership and management.

Complexity theory and curriculum reforms in Hong Kong - Morrison, Keith (Pedagogy, Culture & Society, 2003)

Chatting about chatting - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Many employers in Macau expect their employees to have received higher education (HE). This returns to the endless question of what HE is for; is it for job knowledge and skills acquisition, attitude development, thinking abilities, creativity, problem solving, how to learn, or what? What and whose knowledge?

Challenges of collborataive blend learning in undergraduate students - Monteiro, Elisa; Morrison, Keith (Education Research and Evaluation, 2014)

Causation in educational research - Morrison, Keith (Routledge, 2009)
Keywords: Causation; Education; Research

And the award goes to... - Morrison, Keith (Macau Business, 2022)
Macau, MNA, Opinion | The Macau government recently approved its first reading of a new bill to attract Macau locals to return to Macau to work. Simultaneously, Macau’s Secretary for Social Affairs and Culture was reported as saying that if Macau could create a better environment and conditions, then ‘local talents who are abroad will surely be interested in returning to Macau’.

Alcatraz revisited - Morrison, Keith (Macau Business, 2022)

A risky new year - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Despite the welcome optimism expressed at the government’s plans to resurrect Macau’s economy, its economic recovery will continue to suffer from having had the rug pulled from under its feet by the zero-Covid policy, however well intentioned.

A guide to teaching practice - Cohen, Louis; Manion, Lawrence; Morrison, Keith (Routledge, 1996)
Keywords: Great Britain; Student teaching; Teachers; Training of

A guide to teaching practice - Cohen, Louis; Manion, Lawrence; Morrison, Keith; Wyse, Dominic (Routledge, 2010)
Keywords: Great Britain; Student teaching; Teachers; Training of

A dose of lateral thinking - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | The late psychologist, business and management consultant Edward de Bono gained a worldwide reputation for ‘lateral thinking’, which included his ‘six thinking hats’ and ‘tools for thinking’. Though his work is arguably only plausible pseudoscience, his ‘tools for thinking’ remain interesting. Consider some of these from his Cognitive Research Trust (CoRT), in approaching planning, e.g.: CAF (Consider All Factors); EBS (Examine Both Sides); and OPV (consider Other People’s Views). Here I apply them to Macau.

A Christmas present worth having - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | When the casino resorts applied for the first licenses to operate in Macau, one of the commitments that they made was to serve the Macau society. Many of them have honoured those commitments outstandingly well, and continue to do so, and in ways too many and diverse to list here.